Separator for non-aqueous secondary battery, and non-aqueous secondary battery
By using porous substrates and porous layers of separators in non-aqueous secondary batteries, the problem of detecting position offset between electrodes and separators and insufficient impact resistance of the battery is solved, and the safety and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202380035955.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-27
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively detect the positional deviation between the electrode and the separator, resulting in the risk of battery short circuit and fire, and there is a lack of effective methods to improve battery impact resistance and cycle life.
A separator for a non-aqueous secondary battery is used, which has a porous base material and a porous layer, including resin and barium compound particles. The average particle size of the barium compound particles is between 0.30 μm and 0.50 μm, and the volume ratio occupied is 5. % to 70%, and electromotive force is obtained by doping and dedoping of lithium ions to improve the detectability and performance of the battery.
The positional deviation between the electrode and the separator is achieved through X-ray detection, which improves the impact resistance and circulation characteristics of the battery, reduces the risk of short circuit and fire, and extends the service life of the battery.
Smart Images

Figure BDA0005098701110000171 
Figure BDA0005098701110000281
Abstract
Description
Technical Field
[0001] The present disclosure relates to a separator for a nonaqueous secondary battery and a nonaqueous secondary battery. Background Art
[0002] Patent document 1 discloses a battery separator having a heat-resistant porous layer containing barium sulfate particles and an organic synthetic resin component, wherein the content of the barium sulfate particles contained in the heat-resistant porous layer is 70 volume % or more and 96 volume % or less of the total volume of the barium sulfate particles and the organic synthetic resin component, and the heat-resistant porous layer has a heat-resistant porous layer. 2 Above 19.8g / m 2 the following.
[0003] Patent document 2 discloses a separator for a lithium secondary battery, which contains an X-ray detectable component, wherein the X-ray detectable component contains a mixture of at least two components selected from the group consisting of metals, metal oxides, metal phosphates, metal carbonates, X-ray fluorescent substances, metal salts, metal sulfates, and mixtures thereof.
[0004] Patent Document 3 discloses a separator for a nonaqueous secondary battery, wherein the average primary particle size of barium sulfate particles contained in a heat-resistant porous layer is 0.01 μm or more and less than 0.30 μm.
[0005] Patent Document 1: International Publication No. 2021 / 029397
[0006] Patent Document 2: Japanese Patent Application Publication No. 2021-093376
[0007] Patent Document 3: International Publication No. 2019 / 146155 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Misalignment of the electrodes and separators inside the battery is a cause of battery short circuits and fires. In order to improve battery safety, a technology is required to detect misalignment of the electrodes and separators from outside the battery during the battery manufacturing process.
[0010] The current collector of the electrode is usually a metal foil that does not transmit X-rays. The position of the electrode inside the battery can be detected from the outside of the battery by using X-ray irradiation photography (such as X-ray CT (X-ray Computed Tomography)). In addition, if the separator is a separator with low X-ray transmittance, the positional deviation of the electrode and the separator can be detected from the outside of the battery by using X-ray irradiation photography.
[0011] In order to prevent short circuit and fire of the battery, it is also important for the battery to withstand mechanical impact from the outside.
[0012] The length of the battery cycle life is a performance that is naturally required of secondary batteries.
[0013] The present disclosure is made in view of the above circumstances.
[0014] An object of the present disclosure is to provide a separator for a non-aqueous secondary battery that can detect positional displacement from an electrode using X-rays and improve the impact resistance and cycle characteristics of the battery.
[0015] Means for solving problems
[0016] Specific means for solving the above-mentioned problems include the following aspects.
[0017] <1> A separator for a non-aqueous secondary battery, comprising:
[0018] a porous substrate; and
[0019] A porous layer, which is disposed on one or both sides of the porous substrate and contains a resin and barium compound particles.
[0020] The barium compound particles contained in the porous layer have an average primary particle size of 0.30 μm or more and less than 0.50 μm, and the volume ratio of the barium compound particles in the volume of the porous layer excluding pores is greater than 5 volume % and less than 70 volume %.
[0021] <2> The nonaqueous secondary battery separator according to <1>, wherein the barium compound particles include barium sulfate particles.
[0022] <3> The nonaqueous secondary battery separator according to <1> or <2>, wherein the resin comprises a polyvinylidene fluoride resin.
[0023] <4> The non-aqueous secondary battery separator according to any one of <1> to <3>, wherein the resin comprises at least one selected from the group consisting of wholly aromatic polyamide, polyamideimide, poly-N-vinylacetamide, polyacrylamide, copolymer polyether polyamide, polyimide and polyetherimide.
[0024] <5> The nonaqueous secondary battery separator according to any one of <1> to <4>, wherein the weight per unit area of the porous layer is 2.0 g / m2 in total on both sides of the porous substrate. 2 Above 20.0g / m 2 the following.
[0025] <6> The nonaqueous secondary battery separator according to any one of <1> to <5>, wherein the weight per unit area of the barium compound particles contained in the porous layer is 0.3 g / m in total on both sides of the porous substrate. 2 Above 19.0g / m 2 the following.
[0026] <7> A non-aqueous secondary battery comprising a positive electrode, a negative electrode, and the non-aqueous secondary battery separator according to any one of <1> to <6> disposed between the positive electrode and the negative electrode, wherein the non-aqueous secondary battery obtains an electromotive force by doping and dedoping lithium ions.
[0027] Effects of the Invention
[0028] According to the present disclosure, a separator for a non-aqueous secondary battery is provided, which can detect positional displacement from an electrode by using X-rays and improve the impact resistance and cycle characteristics of the battery. DETAILED DESCRIPTION
[0029] The following describes embodiments of the present disclosure. These descriptions and examples illustrate the embodiments and do not limit the scope of the embodiments.
[0030] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0031] In the numerical range recorded in stages in this disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.
[0032] In the present disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.
[0033] In the present disclosure, when referring to the amount of each component in a composition, if there are multiple substances belonging to each component in the composition, unless otherwise specified, it means the total amount of the multiple substances present in the composition.
[0034] In the present disclosure, particles belonging to each component may contain multiple types. When multiple types of particles belonging to each component are present in the composition, the particle size of each component refers to a value for a mixture of the multiple types of particles present in the composition unless otherwise specified.
[0035] In the present disclosure, the so-called MD (machine direction) refers to the longitudinal direction in the porous substrate and separator manufactured into a long strip, and the so-called TD (transverse direction) refers to the direction perpendicular to the MD in the surface direction of the porous substrate and separator. In the present disclosure, TD is also referred to as the "width direction".
[0036] In the present disclosure, when the stacking relationship of the layers constituting the separator is expressed as “upper” and “lower”, the layer closer to the porous substrate is referred to as “lower” and the layer farther from the porous substrate is referred to as “upper”.
[0037] In the present disclosure, the volume of the porous layer excluding pores is referred to as “solid content volume”.
[0038] <Separators for non-aqueous secondary batteries>
[0039] The non-aqueous secondary battery separator of the present disclosure (also referred to as "separator" in the present disclosure) comprises: a porous substrate; and a porous layer, the porous layer being disposed on one or both sides of the porous substrate and containing resin and barium compound particles. The porous layer is preferably the outermost layer of the separator disposed on one or both sides of the porous substrate.
[0040] The description of the porous layer in the present disclosure is a description of the porous layer on each side of the porous substrate. The separator of the present disclosure only needs to have a porous layer containing resin and barium compound particles on at least one side of the porous substrate. As embodiments of the separator of the present disclosure, the following embodiments (1) to (3) can be cited.
[0041] (1) A separator having porous layers containing a resin and barium compound particles on both surfaces of a porous substrate. In this separator, the porous layer on one surface may be the same as or different from the porous layer on the other surface in terms of components and / or composition.
[0042] (2) A separator having a porous layer containing a resin and barium compound particles on one surface of a porous substrate and another layer on the other surface of the porous substrate.
[0043] (3) A separator having a porous layer containing a resin and barium compound particles on one surface of a porous substrate and having no layer on the other surface of the porous substrate (ie, the surface of the porous substrate is exposed).
[0044] The separator of the present disclosure has a porous layer containing a resin and barium compound particles. Since the X-ray transmittance of the barium compound is low, the porous layer containing an appropriate amount of barium compound particles can be detected by X-ray irradiation photography (eg X-ray CT).
[0045] Examples of the barium compound particles contained in the porous layer include barium sulfate particles, barium carbonate particles, barium titanate particles, barium oxide particles, barium peroxide particles, and barium nitrate particles. The barium compound particles may be used alone or in combination of two or more.
[0046] The separator of the present disclosure includes a porous layer containing a resin and barium compound particles. The average primary particle size of the barium compound particles contained in the porous layer is 0.30 μm or more and less than 0.50 μm.
[0047] When the average primary particle size of the barium compound particles contained in the porous layer is less than 0.30 μm, the cycle characteristics of the battery are poor. From the viewpoint of improving the cycle characteristics of the battery, the average primary particle size of the barium compound particles contained in the porous layer is 0.30 μm or more, preferably 0.32 μm or more, more preferably 0.35 μm or more, and further preferably 0.38 μm or more.
[0048] When the average primary particle size of the barium compound particles contained in the porous layer is 0.50 μm or more, the impact resistance of the battery is poor. From the viewpoint of improving the impact resistance of the battery, the average primary particle size of the barium compound particles contained in the porous layer is less than 0.50 μm, preferably 0.48 μm or less, more preferably 0.45 μm or less, and further preferably 0.42 μm or less.
[0049] From the viewpoint of achieving both the cycle characteristics and the impact resistance of the battery, the average primary particle size of the barium compound particles contained in the porous layer is greater than or equal to 0.30 μm and less than 0.50 μm, preferably greater than or equal to 0.32 μm and less than or equal to 0.48 μm, more preferably greater than or equal to 0.35 μm and less than or equal to 0.45 μm, and further preferably greater than or equal to 0.38 μm and less than or equal to 0.42 μm.
[0050] The average primary particle size of the barium compound particles contained in the porous layer is obtained by measuring the major diameters of 100 barium compound particles randomly selected in the observation based on the scanning electron microscope (SEM), and averaging the 100 major diameters. The sample provided for SEM observation is the barium compound particles as the material for forming the porous layer, or the barium compound particles taken out from the porous layer of the diaphragm. There is no limitation on the method of taking out the barium compound particles from the porous layer of the diaphragm. The method is, for example, a method of immersing the porous layer peeled off from the diaphragm in an organic solvent that can dissolve the resin, dissolving the resin with the organic solvent, and taking out the barium compound particles; a method of heating the porous layer peeled off from the diaphragm to about 800°C to make the resin disappear and take out the barium compound particles; and the like.
[0051] The separator of the present disclosure includes a porous layer containing a resin and barium compound particles, wherein the volume ratio of the barium compound particles in the solid content volume of the porous layer is greater than 5 volume % and less than 70 volume %.
[0052] When the volume ratio of the barium compound particles in the solid component volume of the porous layer is 5 volume % or less, it is difficult to detect the separator inside the battery by X-ray from the outside of the battery, and the impact resistance of the battery is poor. From the viewpoint of being able to detect by X-ray and improving the impact resistance of the battery, the volume ratio of the barium compound particles in the solid component volume of the porous layer is greater than 5 volume %, preferably 20 volume % or more, more preferably 30 volume % or more, and further preferably 40 volume % or more.
[0053] When the volume ratio of the barium compound particles in the solid component volume of the porous layer is 70 volume % or more, the cycle characteristics of the battery are poor. From the viewpoint of improving the cycle characteristics of the battery, the volume ratio of the barium compound particles in the solid component volume of the porous layer is less than 70 volume %, preferably 68 volume % or less, more preferably 65 volume % or less, and further preferably 63 volume % or less.
[0054] From the viewpoint of simultaneously achieving X-ray-based detection and the impact resistance and cycle characteristics of the battery, the volume ratio of the barium compound particles in the solid component volume of the porous layer is greater than 5 volume % and less than 70 volume %, preferably greater than 20 volume % and less than 68 volume %, more preferably greater than 30 volume % and less than 65 volume %, and further preferably greater than 40 volume % and less than 63 volume %.
[0055] The volume ratio V (volume %) of the barium compound particles in the solid content volume of the porous layer is calculated by the following formula.
[0056] V={(Xa / Da) / (Xa / Da+Xb / Db+Xc / Dc+…+Xn / Dn)}×100
[0057] Here, among the constituent materials of the porous layer, the barium compound particles are a, and the other constituent materials are b, c, ..., n. The mass of each constituent material contained in the porous layer of a predetermined area is Xa, Xb, Xc, ..., Xn (g), and the true density of each constituent material is Da, Db, Dc, ..., Dn (g / cm 3 ).
[0058] Xa etc. substituted into the above formula is the mass (g) of the constituent material used to form the porous layer of a predetermined area, or the mass (g) of the constituent material taken out from the porous layer of a predetermined area.
[0059] Da, etc., substituted into the above formula, is the true density (g / cm 3 ), or the true density (g / cm 3 ).
[0060] The weight per unit area of the barium compound particles contained in the porous layer is preferably 0.3 g / m2 in total on both sides of the porous substrate. 2 The weight per unit area of the barium compound particles is 0.3 g / m 2 When the above value is 0.5 g / m, it is easy to detect the separator inside the battery by X-ray from the outside of the battery. From this point of view, the weight per unit area of the barium compound particles contained in the porous layer is more preferably 0.5 g / m 2 More preferably, 1.0 g / m 2 Above, particularly preferably 1.5 g / m 2 above.
[0061] The weight per unit area of the barium compound particles contained in the porous layer is preferably 19.0 g / m2 in total on both sides of the porous substrate. 2 The weight per unit area of the barium compound particles is 19.0 g / m 2 When the weight per unit area of the barium compound particles contained in the porous layer is less than 17.0 g / m, the porous layer can be easily formed with high uniformity, and the cycle characteristics of the battery are improved. From this viewpoint, the weight per unit area of the barium compound particles contained in the porous layer is more preferably 17.0 g / m 2 Below, more preferably 15.0g / m 2 Below, particularly preferably 10.0 g / m 2 the following.
[0062] The weight per unit area of the barium compound particles contained in the porous layer is preferably 0.3 g / m2 in total on both sides of the porous substrate. 2 Above 19.0g / m 2 Below, more preferably 0.5g / m 2 Above 17.0g / m 2 Below, more preferably 1.0 g / m 2 Above 15.0g / m 2 Below, particularly preferably 1.5 g / m 2 Above 10.0g / m 2 the following.
[0063] The weight per unit area (g / m 2 ) refers to the mass of the barium compound particles contained in the porous layer per unit area, with the area of the porous layer being viewed from above being the unit area.
[0064] As the barium compound particles contained in the porous layer, barium sulfate particles are preferred. Barium sulfate particles are not easy to decompose the electrolyte or electrolyte, and are not easy to cause gas generation. Therefore, when the barium compound particles contained in the porous layer are barium sulfate particles, the cycle characteristics of the battery are excellent.
[0065] From the perspective of achieving both the cycle characteristics and impact resistance of the battery, the average primary particle size of the barium sulfate particles contained in the porous layer is preferably greater than 0.30 μm and less than 0.50 μm, more preferably greater than 0.32 μm and less than 0.48 μm, further preferably greater than 0.35 μm and less than 0.45 μm, and particularly preferably greater than 0.38 μm and less than 0.42 μm.
[0066] From the viewpoint of simultaneously achieving X-ray-based detection and the impact resistance and cycle characteristics of the battery, the volume ratio of the barium sulfate particles in the solid component volume of the porous layer is preferably greater than 5 volume % and less than 70 volume %, more preferably greater than 20 volume % and less than 68 volume %, further preferably greater than 30 volume % and less than 65 volume %, and particularly preferably greater than 40 volume % and less than 63 volume %.
[0067] The weight of the barium sulfate particles contained in the porous layer is preferably 0.3 g / m2 in total on both sides of the porous substrate. 2 Above 19.0g / m 2 Below, more preferably 0.5g / m 2 Above 17.0g / m 2 Below, more preferably 1.0 g / m 2 Above 15.0g / m 2 Below, particularly preferably 1.5 g / m 2 Above 10.0g / m 2 the following.
[0068] Hereinafter, the porous substrate and the porous layer included in the separator of the present disclosure will be described in detail.
[0069] [Porous substrate]
[0070] In the present disclosure, the so-called porous substrate refers to a substrate having pores or voids inside. Examples of such substrates include microporous membranes; porous sheets such as non-woven fabrics and paper formed of fibrous materials; composite porous sheets obtained by laminating one or more other porous layers on these microporous membranes or porous sheets; and the like. In the present disclosure, from the perspective of thin film and strength of the diaphragm, a microporous membrane is preferred. The so-called microporous membrane refers to the following membrane: a structure formed with a large number of micropores inside and the micropores are connected, and gas or liquid can pass from one side of the surface to the other side.
[0071] The material of the porous base material is preferably an electrically insulating material, and may be an organic material or an inorganic material.
[0072] In order to impart a shutdown function to the porous substrate, the porous substrate preferably contains a thermoplastic resin. The so-called shutdown function refers to the following function: when the battery temperature rises, the constituent material melts and blocks the pores of the porous substrate, thereby blocking the migration of ions and preventing thermal runaway of the battery. As a thermoplastic resin, a thermoplastic resin with a melting point below 200°C is preferred. As thermoplastic resins, polyesters such as polyethylene terephthalate; polyolefins such as polyethylene and polypropylene; etc. can be cited, among which polyolefins are preferred.
[0073] The porous substrate is preferably a microporous membrane comprising polyolefin (referred to as "polyolefin microporous membrane" in this disclosure). Examples of the polyolefin microporous membrane include polyolefin microporous membranes suitable for existing battery separators, and it is preferred to select a polyolefin microporous membrane having sufficient mechanical properties and ion permeability.
[0074] From the viewpoint of exhibiting the shutdown function, the polyolefin microporous membrane is preferably a microporous membrane containing polyethylene, and the content of polyethylene is preferably 95% by mass or more based on the total mass of the polyolefin microporous membrane.
[0075] The polyolefin microporous membrane is preferably a microporous membrane made of polypropylene from the viewpoint of having heat resistance such that the membrane is less likely to be damaged when exposed to high temperatures.
[0076] From the viewpoint of having a shutdown function and heat resistance that is not prone to film breakage when exposed to high temperatures, the polyolefin microporous membrane is preferably a polyolefin microporous membrane comprising polyethylene and polypropylene. As a polyolefin microporous membrane comprising polyethylene and polypropylene, a microporous membrane in which polyethylene and polypropylene are mixed in one layer can be cited. In the microporous membrane, from the viewpoint of realizing the shutdown function and heat resistance at the same time, it is preferred to contain more than 95% by mass of polyethylene and less than 5% by mass of polypropylene. In addition, from the viewpoint of realizing the shutdown function and heat resistance at the same time, a polyolefin microporous membrane of the following structure is also preferred: having a laminated structure of more than 2 layers, at least 1 layer containing polyethylene, and at least 1 layer containing polypropylene.
[0077] As the polyolefin contained in the polyolefin microporous membrane, a polyolefin having a weight average molecular weight (Mw) of 100,000 to 5,000,000 is preferred. If the Mw of the polyolefin is 100,000 or more, sufficient mechanical properties can be imparted to the microporous membrane. On the other hand, if the Mw of the polyolefin is 5,000,000 or less, the shutdown properties of the microporous membrane are good, and the microporous membrane is easily molded.
[0078] As a method for manufacturing a polyolefin microporous membrane, the following methods can be cited: a method of extruding a molten polyolefin resin from a T-die to form a sheet, subjecting the sheet to a crystallization treatment, then stretching the sheet, and then heat treating the sheet to form a microporous membrane; a method of extruding a polyolefin resin melted together with a plasticizer such as liquid paraffin from a T-die, cooling the sheet to form a sheet, stretching the sheet to extract the plasticizer, and heat treating the sheet to form a microporous membrane; and the like.
[0079] Examples of porous sheets formed from fibrous materials include nonwoven fabrics, paper, and other porous sheets formed from fibrous materials of the following substances: polyesters such as polyethylene terephthalate; polyolefins such as polyethylene and polypropylene; heat-resistant resins such as wholly aromatic polyamides, polyamide-imides, polyimides, polyether sulfones, polysulfones, polyether ketones, and polyether imides; cellulose; and the like.
[0080] In the present disclosure, the heat-resistant resin refers to a resin having a melting point of 200° C. or higher, or a resin having no melting point but a decomposition temperature of 200° C. or higher. In other words, the heat-resistant resin in the present disclosure refers to a resin that does not melt or decompose in a temperature range below 200° C.
[0081] As a composite porous sheet, a sheet obtained by laminating a functional layer on a porous sheet formed of a microporous membrane or a fibrous material can be cited. From the viewpoint that further functions can be added through the functional layer, such a composite porous sheet is preferred. As a functional layer, for example, from the viewpoint of imparting heat resistance, a porous layer formed of a heat-resistant resin, a porous layer formed of a heat-resistant resin and an inorganic filler can be cited. As a heat-resistant resin, one or more heat-resistant resins selected from wholly aromatic polyamides, polyamide-imides, polyimides, polyether sulfones, polysulfones, polyether ketones and polyether imides can be cited. As an inorganic filler, metal oxides such as aluminum oxide; metal hydroxides such as magnesium hydroxide; and the like can be cited. Examples of composite methods include: coating a functional layer on a microporous membrane or a porous sheet; bonding a microporous membrane or a porous sheet to the functional layer with an adhesive; thermally pressing the microporous membrane or a porous sheet to the functional layer; and the like.
[0082] For the purpose of improving the wettability with the coating liquid for forming the porous layer, various surface treatments can be applied to the surface of the porous substrate within the range of not damaging the properties of the porous substrate. As surface treatments, corona treatment, plasma treatment, flame treatment, ultraviolet irradiation treatment, etc. can be cited.
[0083] [Characteristics of porous substrate]
[0084] As for the thickness of the porous substrate, from the viewpoint of improving the energy density of the battery, it is preferably less than 25 μm, more preferably less than 20 μm, and further preferably less than 15 μm. From the viewpoint of the manufacturing yield of the separator and the manufacturing yield of the battery, it is preferably more than 3 μm, more preferably more than 5 μm, and further preferably more than 8 μm.
[0085] The thickness (μm) of the porous substrate was determined by measuring 20 points within a 10 cm square using a contact thickness gauge (Mitutoyo Co., Ltd., LITEMATI C VL-50S) and averaging them. The measurement terminal used a spherical probe (Mitutoyo Co., Ltd.) with a ball radius of 10 mm, and was adjusted to apply a load of 0.19 N during the measurement.
[0086] From the viewpoint of suppressing short circuit of the battery, the Gurley value (JIS P8117:2009) of the porous substrate is preferably 20 sec / 100 mL or more, more preferably 25 sec / 100 mL or more, further preferably 60 sec / 100 mL or more, and particularly preferably 65 sec / 100 mL or more.
[0087] From the viewpoint of ion permeability and the viewpoint of suppressing clogging of the porous structure at the boundary between the porous substrate and the porous layer when exposed to high temperature, the Gurley value (JIS P8117:2009) of the porous substrate is preferably 220 seconds / 100 mL or less, more preferably 200 seconds / 100 mL or less, further preferably 160 seconds / 100 mL or less, and particularly preferably 150 seconds / 100 mL or less.
[0088] The Gurley value (seconds / 100 mL) of the porous substrate was measured in accordance with JIS P8117:2009 using a Gurley air permeability tester (Toyo Seiki Co., Ltd., G-B2C).
[0089] From the viewpoint of obtaining appropriate membrane resistance and shutdown function, the porosity of the porous substrate is preferably 20% to 60%. The porosity ε (%) of the porous substrate is calculated by the following formula.
[0090] ε={1-Ws / (ds·t)}×100
[0091] Here, Ws is the weight per unit area of the porous substrate (g / m 2 ), ds is the true density of the porous substrate (g / cm 3 ), t is the thickness of the porous substrate (μm). Weight per unit area refers to the mass per unit area.
[0092] From the viewpoint of ion permeability or suppression of battery short circuit, the average pore size of the porous substrate is preferably 15 nm to 100 nm. The average pore size of the porous substrate is measured using a palm porometer (CFP-1500-A manufactured by PMI) in accordance with ASTM E1294-89.
[0093] [Porous layer]
[0094] The porous layer is a layer having a large number of micropores inside, and having a structure in which the micropores are connected, so that gas or liquid can pass from one surface to the other surface.
[0095] The porous layer may be present only on one side of the porous substrate or on both sides of the porous substrate. If the porous layer is present on both sides of the porous substrate, it is not easy to curl in the separator, and the operability during the manufacture of the battery is excellent. If the porous layer is present only on one side of the porous substrate, the ion permeability of the separator is more excellent. In addition, the thickness of the separator as a whole can be suppressed, and a battery with higher energy density can be manufactured.
[0096] The porous layer contains at least a resin and barium compound particles. The porous layer may contain other particles in addition to the barium compound particles. The other particles may be either inorganic particles or organic particles.
[0097] The resin contained in the porous layer has the following functions, for example: bonding particles contained in the porous layer to each other; bonding the porous layer to the porous substrate; bonding the porous layer to the electrode; and improving the heat resistance of the porous layer.
[0098] -Polyvinylidene fluoride resin-
[0099] An example of the resin contained in the porous layer is a polyvinylidene fluoride resin. When the resin contained in the porous layer is a polyvinylidene fluoride resin, the ion permeability of the porous layer is high, and the cycle characteristics of the battery are good.
[0100] Examples of polyvinylidene fluoride resins include homopolymers of vinylidene fluoride (i.e., polyvinylidene fluoride); copolymers of vinylidene fluoride and halogen-containing monomers such as hexafluoropropylene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, vinyl fluoride, and trichloroethylene; copolymers of vinylidene fluoride and other monomers other than halogen-containing monomers; copolymers of vinylidene fluoride and halogen-containing monomers and other monomers other than halogen-containing monomers; and mixtures thereof. The polyvinylidene fluoride resins may be used alone or in combination of two or more.
[0101] As polyvinylidene fluoride resin, from the viewpoint of adhesion to the electrode, preferably a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (VDF-HFP copolymer). In the present disclosure, VDF-HFP copolymer includes any copolymer obtained by polymerizing VDF and HFP alone, and any copolymer obtained by polymerizing VDF and HFP with other monomers. For VDF-HFP copolymer, by increasing or decreasing the content of HFP unit, the crystallinity, heat resistance, solubility resistance to electrolyte, etc. of the copolymer can be controlled within a moderate range.
[0102] From the viewpoint that clogging of the pores of the porous layer is less likely to occur when heat is applied to the porous layer during battery manufacturing, the weight average molecular weight (Mw) of the polyvinylidene fluoride resin contained in the porous layer as a whole is preferably 300,000 or more, more preferably 500,000 or more, further preferably 650,000 or more, and particularly preferably 750,000 or more.
[0103] From the viewpoint that the polyvinylidene fluoride resin is moderately softened when heat is applied to the porous layer during battery manufacturing and the porous layer and the electrode are well bonded, the Mw of the polyvinylidene fluoride resin contained in the porous layer as a whole is preferably less than 3 million, more preferably less than 2.5 million, further preferably less than 2 million, and particularly preferably less than 1 million.
[0104] The Mw of the entire polyvinylidene fluoride resin contained in the porous layer is a molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The polyvinylidene fluoride resin extracted from the porous layer or the polyvinylidene fluoride resin used to form the porous layer is used as a sample.
[0105] When the porous layer contains a polyvinylidene fluoride resin, the content of the polyvinylidene fluoride resin is preferably 85% to 100% by mass, more preferably 90% to 100% by mass, and further preferably 95% to 100% by mass, relative to the total amount of all resins contained in the porous layer.
[0106] When the porous layers are located on both surfaces of the porous substrate, the type or amount of the polyvinylidene fluoride-based resin contained in one porous layer may be the same as or different from the type or amount of the polyvinylidene fluoride-based resin contained in the other porous layer.
[0107] -Heat-resistant resin-
[0108] As an example of the resin contained in the porous layer, a heat-resistant resin can be cited. The type of the heat-resistant resin is not limited as long as it is a resin that does not melt or decompose in a temperature range below 200° C. When the resin contained in the porous layer is a heat-resistant resin, the porous layer has high heat resistance and the impact resistance of the battery is improved.
[0109] As the heat-resistant resin, at least one selected from the group consisting of wholly aromatic polyamide, polyamide-imide, poly-N-vinyl acetamide, polyacrylamide, copolymerized polyether polyamide, polyimide and polyether imide can be cited. These resins can be used alone or in combination of two or more. When the resin contained in the porous layer is at least one of these resins, the heat resistance of the porous layer is high and the impact resistance of the battery is improved.
[0110] Among the heat-resistant resins, fully aromatic polyamides are preferred from the viewpoint of durability. The so-called fully aromatic polyamide refers to a polyamide whose main chain is composed only of benzene rings and amide bonds. Among them, a small amount of aliphatic monomers can also be copolymerized in the fully aromatic polyamide. Fully aromatic polyamides are also called aromatic polyamides.
[0111] The wholly aromatic polyamide may be a meta-type or a para-type. Among the wholly aromatic polyamides, the meta-type wholly aromatic polyamide is preferred from the viewpoint of easy formation of a porous layer and excellent redox resistance in an electrode reaction. Specifically, the wholly aromatic polyamide is preferably poly(m-phenylene isophthalamide) or poly(p-phenylene terephthalamide), and more preferably poly(m-phenylene isophthalamide).
[0112] When the porous layer contains a heat-resistant resin, the content of the heat-resistant resin is preferably 85% to 100% by mass, more preferably 90% to 100% by mass, and further preferably 95% to 100% by mass, relative to the total amount of all resins contained in the porous layer.
[0113] When the porous layer contains wholly aromatic polyamide, the content of wholly aromatic polyamide is preferably 85% to 100% by mass, more preferably 90% to 100% by mass, and further preferably 95% to 100% by mass, relative to the total amount of all resins contained in the porous layer.
[0114] When the porous layers are located on both surfaces of the porous substrate, the type or amount of the heat-resistant resin contained in one porous layer may be the same as or different from the type or amount of the heat-resistant resin contained in the other porous layer.
[0115] -Other resins-
[0116] The porous layer may contain other resins except polyvinylidene fluoride resin and heat-resistant resin. As other resins, for example, homopolymers or copolymers of acrylic resins, fluorine-based rubbers, styrene-butadiene copolymers, vinyl nitrile compounds (acrylonitrile, methacrylonitrile, etc.), carboxymethyl cellulose, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyethers (polyethylene oxide, polypropylene oxide, etc.), polysulfones, polyketones, polyether ketones, polyether sulfones, and mixtures thereof may be cited.
[0117] The content of other resins contained in the porous layer is preferably 0 to 15% by mass, more preferably 0 to 10% by mass, and further preferably 0 to 5% by mass, based on the total amount of resins contained in the porous layer.
[0118] -Barium compound particles-
[0119] Examples of the barium compound particles contained in the porous layer include barium sulfate particles, barium carbonate particles, barium titanate particles, barium oxide particles, barium peroxide particles, and barium nitrate particles. The barium compound particles may be used alone or in combination of two or more.
[0120] The barium compound particles contained in the porous layer may be particles whose surfaces are modified with a silane coupling agent or the like.
[0121] The particle shape of the barium compound particles contained in the porous layer is not limited, and can be any of spherical, elliptical, plate-like, needle-like, and amorphous. From the viewpoint of suppressing short circuit of the battery, the barium compound particles contained in the porous layer are preferably plate-like particles and non-aggregated primary particles.
[0122] The content of the barium compound particles contained in the porous layer is preferably 85 to 100 mass %, more preferably 90 to 100 mass %, and further preferably 95 to 100 mass %, based on the total amount of the inorganic particles contained in the porous layer.
[0123] When the porous layer contains barium sulfate particles, the content of the barium sulfate particles is preferably 85% to 100% by mass, more preferably 90% to 100% by mass, and further preferably 95% to 100% by mass, relative to the total amount of inorganic particles contained in the porous layer.
[0124] When the porous layers are located on both surfaces of the porous substrate, the type or amount of the barium compound particles contained in one porous layer may be the same as or different from the type or amount of the barium compound particles contained in the other porous layer.
[0125] -Other inorganic particles other than barium compound particles-
[0126] The porous layer may contain other inorganic particles in addition to the barium compound particles. The volume ratio of other inorganic particles in the solid content volume of the porous layer is preferably 5 volume % or less, more preferably 3 volume % or less, further preferably 1 volume % or less, and it is particularly preferred that other inorganic particles are substantially not contained.
[0127] As other inorganic particles, for example, there can be mentioned: particles of metal hydroxides such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, chromium hydroxide, zirconium hydroxide, cerium hydroxide, nickel hydroxide, and boron hydroxide; particles of metal oxides such as silicon dioxide, aluminum oxide, titanium oxide, zirconium oxide, and magnesium oxide; particles of carbonates such as calcium carbonate and magnesium carbonate; particles of sulfates such as calcium sulfate; clay minerals such as calcium silicate and talc; and so on. As other inorganic particles, from the perspective of stability of the electrolyte and electrochemical stability, particles of metal hydroxides or particles of metal oxides are preferred. Other inorganic particles can be surface-modified using silane coupling agents, etc. Other inorganic particles can be used alone or in combination of two or more.
[0128] The particle shape of the other inorganic particles is not limited and may be any of spherical, elliptical, plate-like, needle-like, and amorphous. From the viewpoint of suppressing short circuits of the battery, the other inorganic particles contained in the porous layer are preferably plate-like particles or non-aggregated primary particles.
[0129] The average primary particle size of the other inorganic particles is preferably 0.01 μm to 5.0 μm, and more preferably 0.1 μm to 1.0 μm.
[0130] -Organic particles-
[0131] The porous layer may contain organic particles. Examples of organic particles include particles formed from crosslinked polymers such as crosslinked poly(meth)acrylic acid, crosslinked poly(meth)acrylate, crosslinked polysiloxane, crosslinked polystyrene, crosslinked polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked products, melamine resins, phenolic resins, and benzoguanamine-formaldehyde condensates; particles formed from heat-resistant polymers such as polysulfone, polyacrylonitrile, aromatic polyamide, and polyacetal; and the like. The expression "(meth)acrylic-" means that it can be either "acrylic-" or "methacrylic-".
[0132] The resin constituting the organic particles may be the above-mentioned exemplified materials, mixtures, modified products, derivatives, copolymers (random copolymers, alternating copolymers, block copolymers, graft copolymers) or crosslinked products.
[0133] The organic particles may be used alone or in combination of two or more.
[0134] -Other ingredients-
[0135] The porous layer may contain additives such as dispersants such as surfactants, wetting agents, defoamers, and pH adjusters. The dispersant is added to the coating liquid for forming the porous layer for the purpose of improving dispersibility, coating properties, or storage stability. The wetting agent, defoamer, and pH adjuster are added to the coating liquid for forming the porous layer for the purpose of, for example, improving affinity with the porous substrate, inhibiting air from entering the coating liquid, or adjusting pH.
[0136] [Characteristics of the porous layer]
[0137] From the perspective of the ease of X-ray detection of the diaphragm and the impact resistance of the battery, the thickness of the porous layer is preferably 0.5 μm or more on one side, more preferably 1.0 μm or more on one side, and further preferably 1.5 μm or more on one side. From the perspective of ion permeability and battery energy density, it is preferably 10.0 μm or less on one side, more preferably 8.0 μm or less on one side, and further preferably 6.0 μm or less on one side.
[0138] As for the thickness of the porous layer, when the porous layer is located on both sides of the porous substrate, the total thickness of the two sides of the porous substrate is preferably 1.0 μm or more, more preferably 2.0 μm or more, further preferably 3.0 μm or more, preferably 20.0 μm or less, more preferably 16.0 μm or less, and further preferably 12.0 μm or less.
[0139] When the porous layers are located on both surfaces of the porous substrate, the difference (μm) between the thickness of one porous layer and the thickness of the other porous layer is preferably as small as possible, and is preferably 20% or less of the total thickness (μm) of both surfaces.
[0140] Regarding the weight per unit area (mass per unit area) of the porous layer, whether the porous layer is located on one side or on both sides of the porous substrate, from the perspective of the ease of detection of the separator based on X-rays and the impact resistance of the battery, the total weight of both sides of the porous substrate is preferably 2.0 g / m 2 More preferably 2.5 g / m 2 More preferably, 3.0 g / m 2 More preferably, 3.4 g / m 2 above.
[0141] The weight per unit area (mass per unit area) of the porous layer is preferably 20.0 g / m2 in total for both sides of the porous substrate, regardless of whether the porous layer is located on one side or on both sides of the porous substrate, from the viewpoint of ion permeability, battery energy density, and cycle characteristics.2 Below, more preferably 18.0g / m 2 Below, more preferably 15.0g / m 2 Below, more preferably 10.0 g / m 2 the following.
[0142] When the porous layers are located on both sides of the porous substrate, from the viewpoint of suppressing the curling of the separator or improving the cycle characteristics of the battery, the difference (g / m 2 ) is preferably as small as possible, and is preferably the total amount on both sides of the porous substrate (g / m 2 ) is less than 20%.
[0143] From the viewpoint of ion permeability, the porosity of the porous layer is preferably 30% or more, more preferably 35% or more, and further preferably 40% or more. From the viewpoint of mechanical strength of the porous layer, it is preferably 70% or less, more preferably 65% or less, and further preferably 60% or less. The porosity ε (%) of the porous layer is obtained by the following formula.
[0144] [Mathematical formula 1]
[0145]
[0146] Here, regarding the constituent material 1, constituent material 2, constituent material 3, ..., constituent material n of the porous layer, the mass per unit area of each constituent material is W1, W2, W3, ..., and W4. 2、 W3, ..., W n (g / cm 2 ), the true density of each constituent material is d1, d2, d3, ..., d n (g / cm 3 ), the thickness of the porous layer is t (cm).
[0147] The average pore size of the porous layer is preferably 10 nm to 200 nm. If the average pore size is 10 nm or more, when the electrolyte is impregnated in the porous layer, even if the resin contained in the porous layer swells, it is not easy to cause clogging of the pores. If the average pore size is 200 nm or less, the uniformity of ion migration in the porous layer is high, and the cycle characteristics and load characteristics of the battery are excellent.
[0148] The average pore diameter (nm) of the porous layer was calculated by the following formula assuming that all pores were cylindrical.
[0149] d=4V / S
[0150] In the formula, d represents the average pore size (diameter) of the porous layer, and V represents the number of pores per m 2The pore volume of the porous layer, S represents the pore volume per 1m 2 The pore surface area of the porous layer.
[0151] Every 1m 2 The pore volume V of the porous layer is calculated from the porosity of the porous layer.
[0152] Every 1m 2 The pore surface area S of the porous layer is determined by the following method.
[0153] First, the specific surface area (m2) of the porous substrate was calculated from the amount of nitrogen adsorption by applying the BET formula in the nitrogen adsorption method. 2 / g) and the specific surface area of the membrane (m 2 / g). Their specific surface area (m 2 / g) multiplied by their respective unit area weight (g / m 2 ), calculate the respective 2 Then, from every 1m 2 The pore surface area of the diaphragm is reduced by 2 The pore surface area of the porous substrate is calculated per 1m 2 The pore surface area of the porous layer is S. The so-called weight per unit area is the mass per unit area.
[0154] [Characteristics of diaphragm]
[0155] From the perspective of the mechanical strength of the separator, the thickness of the separator is preferably 8 μm or more, more preferably 10 μm or more, and further preferably 12 μm or more. From the perspective of the energy density of the battery, it is preferably 25 μm or less, more preferably 22 μm or less, and further preferably 20 μm or less.
[0156] From the viewpoint of suppressing short circuit of the battery, the Gurley value (JIS P8117:2009) of the separator is preferably 50 sec / 100 mL or more, more preferably 60 sec / 100 mL or more, further preferably 70 sec / 100 mL or more, and particularly preferably 80 sec / 100 mL or more.
[0157] From the viewpoint of ion permeability, the Gurley value (JIS P8117:2009) of the separator is preferably 200 sec / 100 mL or less, more preferably 180 sec / 100 mL or less, further preferably 150 sec / 100 mL or less, and particularly preferably 130 sec / 100 mL or less.
[0158] From the viewpoint of the load characteristics of the battery, the membrane resistance of the separator is preferably 1 Ω·cm 2 ~10Ω·cm 2The membrane resistance of the diaphragm is the resistance value when the diaphragm is impregnated with an electrolyte, and is a value measured by an alternating current method at 20°C using 1 mol / L LiBF4-propylene carbonate:ethylene carbonate (mass ratio is 1:1) as an electrolyte. The lower the membrane resistance value of the diaphragm, the better the ion permeability of the diaphragm.
[0159] [Method for manufacturing diaphragm]
[0160] The separator of the present disclosure can be manufactured, for example, by forming a porous layer on a porous substrate using a wet coating method or a dry coating method. In the present disclosure, the wet coating method is a method of solidifying the coating layer in a coagulation liquid, and the dry coating method is a method of solidifying the coating layer by drying. An example of an implementation of the wet coating method is described below.
[0161] The wet coating method is a method in which a coating liquid containing a resin and a filler is applied to a porous substrate, the coating layer is solidified by immersing the substrate in a solidifying liquid, the substrate is pulled out of the solidifying liquid, washed with water, and dried.
[0162] The coating liquid for forming the porous layer is prepared by dissolving or dispersing a resin and barium compound particles in a solvent. Other components other than the resin and the barium compound particles may be dissolved or dispersed in the coating liquid as required.
[0163] The solvent used in the preparation of the coating liquid includes a solvent capable of dissolving the resin (hereinafter also referred to as a "good solvent"). Examples of the good solvent include polar amide solvents such as N-methylpyrrolidone, dimethylacetamide, and dimethylformamide.
[0164] From the viewpoint of forming a porous layer with a good porous structure, the solvent used in the preparation of the coating liquid may include a phase separation agent that induces phase separation. Therefore, the solvent used in the preparation of the coating liquid may be a mixed solvent of a good solvent and a phase separation agent. The phase separation agent is preferably mixed with the good solvent in an amount that can ensure a range of viscosity suitable for coating. As the phase separation agent, water, methanol, ethanol, propanol, butanol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, etc. may be cited.
[0165] When the solvent used in the preparation of the coating liquid is a mixed solvent of a good solvent and a phase separation agent, from the viewpoint of forming a good porous structure, the mixed solvent preferably contains 60 mass % or more of the good solvent and 5 mass % to 40 mass % of the phase separation agent.
[0166] From the viewpoint of forming a good porous structure, the resin concentration of the coating liquid is preferably 1 to 20% by mass. From the viewpoint of forming a good porous structure, the barium compound particle concentration of the coating liquid is preferably 0.5 to 50% by mass.
[0167] The coating liquid may contain a dispersant such as a surfactant, a wetting agent, a defoaming agent, a pH adjuster, etc. These additives may remain in the porous layer as long as they are electrochemically stable within the use range of the non-aqueous secondary battery and do not inhibit the reaction in the battery.
[0168] As the coating means for applying the coating liquid to the porous substrate, there can be mentioned a Meyer rod, a die coater, a reverse roll coater, a roll coater, a gravure coater, etc. When a porous layer is formed on both sides of the porous substrate, it is preferred to apply the coating liquid to both sides of the porous substrate at the same time from the viewpoint of productivity.
[0169] The coating layer can be cured by immersing the porous substrate on which the coating layer is formed in a coagulation liquid to cure the resin while inducing phase separation in the coating layer, thereby obtaining a laminate composed of the porous substrate and the porous layer.
[0170] The coagulation liquid generally contains a good solvent and a phase separation agent used in the preparation of the coating liquid, and water. From the production point of view, the mixing ratio of the good solvent and the phase separation agent is preferably consistent with the mixing ratio of the mixed solvent used in the preparation of the coating liquid. From the viewpoint of the formation of the porous structure and productivity, the water content in the coagulation liquid is preferably 40% to 90% by mass. The temperature of the coagulation liquid is, for example, 20°C to 50°C.
[0171] After the coating layer is cured in the coagulation liquid, the laminate is lifted out of the coagulation liquid and washed with water. The coagulation liquid is removed from the laminate by washing with water. Water is further removed from the laminate by drying. Washing with water is performed, for example, by conveying the laminate in a water bath. Drying is performed, for example, by conveying the laminate in a high temperature environment, blowing air on the laminate, or contacting the laminate with a hot roller. The drying temperature is preferably 40°C to 80°C.
[0172] The separator of the present disclosure can also be produced by a dry coating method. The dry coating method is a method in which a coating liquid is applied to a porous substrate, and the coating layer is dried to volatilize and remove the solvent, thereby forming a porous layer on the porous substrate.
[0173] The separator of the present disclosure can also be manufactured by the following method: a porous layer is prepared in the form of an independent sheet, the porous layer is overlapped with a porous substrate, and composited by thermal compression bonding or an adhesive. As a method for preparing a porous layer in the form of an independent sheet, the following method can be cited: a porous layer is formed on a release sheet by applying the above-mentioned wet coating method or dry coating method.
[0174] <Non-aqueous secondary batteries>
[0175] The non-aqueous secondary battery of the present disclosure is a non-aqueous secondary battery that obtains electromotive force by doping and dedoping lithium ions, and comprises a positive electrode, a negative electrode, and a separator for the non-aqueous secondary battery of the present disclosure. The so-called doping refers to absorption, loading, adsorption, or insertion, which refers to the phenomenon that lithium ions enter the active material of the positive electrode and other electrodes.
[0176] The nonaqueous secondary battery of the present disclosure has a structure in which a battery element (a negative electrode and a positive electrode facing each other via a separator) is sealed in an outer packaging material together with an electrolyte. The nonaqueous secondary battery of the present disclosure is suitable for nonaqueous electrolyte secondary batteries, especially lithium ion secondary batteries.
[0177] Hereinafter, examples of the positive electrode, the negative electrode, the electrolyte solution, and the outer casing material included in the non-aqueous secondary battery of the present disclosure will be described.
[0178] As an embodiment of the positive electrode, there can be cited a structure in which an active material layer including a positive electrode active material and a binder resin is formed on a current collector. The active material layer may further include a conductive aid. As the positive electrode active material, there can be cited, for example, a transition metal oxide containing lithium, specifically, LiCoO2, LiNiO2, LiMn 1 / 2 Ni 1 / 2 O2、LiCo 1 / 3Mn 1 / 3 Ni 1 / 3 O2, LiMn2O4, LiFePO4, LiCo 1 / 2 Ni 1 / 2 O2、LiAl 1 / 4 Ni 3 / 4 O2, etc. Examples of binder resins include polyvinylidene fluoride resins and styrene-butadiene copolymers. Examples of conductive additives include carbon materials such as acetylene black, Ketjen black, and graphite powder. Examples of current collectors include aluminum foil, titanium foil, and stainless steel foil with a thickness of 5 μm to 20 μm.
[0179] As an embodiment of the negative electrode, there can be cited a structure in which an active material layer including a negative electrode active material and a binder resin is formed on a current collector. The active material layer may further include a conductive aid. As the negative electrode active material, there can be cited materials that can electrochemically absorb lithium ions, specifically, for example, carbon materials; alloys of lithium with silicon, tin, aluminum, etc.; Wood's alloy; and the like. As a binder resin, for example, polyvinylidene fluoride resins, styrene-butadiene copolymers, etc. can be cited. As a conductive aid, for example, carbon materials such as acetylene black, Ketjen black, graphite powder, and ultrafine carbon fibers can be cited. As a current collector, for example, copper foil, nickel foil, stainless steel foil, etc. with a thickness of 5μm to 20μm can be cited. In addition, metal lithium foil can be used as the negative electrode instead of the above-mentioned negative electrode.
[0180] The electrolyte is a solution obtained by dissolving a lithium salt in a non-aqueous solvent. Examples of lithium salts include LiPF6, LiBF4, and LiClO4. Examples of non-aqueous solvents include cyclic carbonates such as ethylene carbonate, propylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and fluorinated carbonates thereof; cyclic esters such as γ-butyrolactone and γ-valerolactone; and the like, which can be used alone or in combination. As an electrolyte, a solution obtained by mixing cyclic carbonates and chain carbonates in a mass ratio of 20:80 to 40:60 (cyclic carbonate: chain carbonate) and dissolving lithium salts in a range of 0.5 mol / L to 1.5 mol / L is suitable.
[0181] Examples of the outer packaging material include aluminum laminated film packaging, metal cases, etc. The shape of the battery includes a square shape, a cylindrical shape, a button shape, etc. The separator of the present disclosure is suitable for any shape.
[0182] The non-aqueous secondary battery of the present disclosure can be manufactured by manufacturing a laminated body in which the separator of the present disclosure is arranged between the positive electrode and the negative electrode, and then using the laminated body to manufacture by any of the following methods (1) to (3). In the following description, hot pressing after impregnating the separator with an electrolyte is referred to as "wet hot pressing", and hot pressing without impregnating the separator with an electrolyte is referred to as "dry hot pressing".
[0183] (1) After the stack is dry-hot pressed to bond the electrode and the separator, it is placed in an outer packaging material (e.g., an aluminum laminate film package, the same below), and an electrolyte is injected into the outer packaging material to make the outer packaging material a vacuum state. The stack is then further wet-hot pressed from the outside of the outer packaging material to bond the electrode and the separator and to seal the outer packaging material.
[0184] (2) The stack is placed in an outer packaging material, an electrolyte is injected therein, and after the outer packaging material is made into a vacuum state, the stack is wet-hot pressed from the outside of the outer packaging material to bond the electrode and the separator and seal the outer packaging material.
[0185] (3) After the stacked body is dry-heat-pressed to bond the electrodes and the separator, it is placed in an outer packaging material, an electrolyte is injected therein, and after the inside of the outer packaging material is made into a vacuum state, the outer packaging material is sealed.
[0186] As the conditions for wet hot pressing in the above-mentioned manufacturing method, the pressing temperature is preferably 70°C to 110°C, and the pressing pressure is preferably 0.5MPa to 2MPa. As the conditions for dry hot pressing in the above-mentioned manufacturing method, the pressing temperature is preferably 20°C to 100°C, and the pressing pressure is preferably 0.5MPa to 9MPa. The pressing time is preferably adjusted according to the pressing temperature and the pressing pressure, for example, in the range of 0.5 minutes to 60 minutes.
[0187] When manufacturing a stacked body in which a separator is arranged between a positive electrode and a negative electrode, the method of arranging the separator between the positive electrode and the negative electrode can be a method in which the positive electrode, the separator, and the negative electrode are stacked in sequence in at least one layer (the so-called stacking method), or a method in which the positive electrode, the separator, the negative electrode, and the separator are overlapped in sequence and wound along the length direction.
[0188] Example
[0189] Hereinafter, the separator and the non-aqueous secondary battery of the present disclosure are described in more detail by way of examples. The materials, usage amounts, ratios, processing steps, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the separator and the non-aqueous secondary battery of the present disclosure should not be interpreted restrictively based on the specific examples shown below.
[0190] In the following description, unless otherwise specified, synthesis, treatment, production, etc. are performed at room temperature (25° C.±3° C.).
[0191] <Measurement method, evaluation method>
[0192] The measuring methods and evaluation methods used in Examples and Comparative Examples are as follows.
[0193] [Thickness of porous substrate]
[0194] The thickness of the porous substrate ( μ m) was obtained by measuring 20 points within a 10 cm square using a contact thickness gauge (Mitutoyo Co., Ltd., LITEMATI C VL-50S) and averaging the results. A spherical probe (Mitutoyo Co., Ltd.) with a ball radius of 10 mm was used as the measurement terminal, and the load was adjusted to apply 0.19 N during the measurement.
[0195] [Porosity of porous substrate]
[0196] The porosity ε (%) of the porous substrate is determined by the following formula.
[0197] ε = {1-W s / (d s ·t)}×100
[0198] Here, Ws is the weight per unit area of the porous substrate (g / m 2 ), ds is the true density of the porous substrate (g / cm 3 ), t is the thickness of the porous substrate (μm). Weight per unit area refers to the mass per unit area.
[0199] [Gurley value of porous substrate]
[0200] The Gurley value (seconds / 100 mL) of the porous substrate was measured in accordance with JIS P8117:2009 using a Gurley densometer (Toyo Seiki Co., Ltd., G-B2C).
[0201] [Average primary particle size of inorganic particles]
[0202] The inorganic particles used for forming the porous layer were prepared as samples and observed under SEM to determine the average primary particle size.
[0203] The average primary particle size of the barium compound particles contained in the porous layer is obtained by measuring the major diameters of 100 barium compound particles randomly selected in observation based on a scanning electron microscope (SEM), and averaging the 100 major diameters. The sample provided for SEM observation is a barium compound particle as a material for forming the porous layer, or a barium compound particle taken out from the porous layer of the separator. There is no limitation on the method for taking out the barium compound particles from the porous layer of the separator.
[0204] [Volume ratio of inorganic particles]
[0205] The volume ratio V (volume %) of the inorganic particles in the solid content volume of the porous layer is calculated by the following formula.
[0206] V={(Xa / Da) / (Xa / Da+Xb / Db+Xc / Dc+…+Xn / Dn)}×100
[0207] Here, among the constituent materials of the porous layer, inorganic particles are a, and other constituent materials are b, c, ..., n. The mass of each constituent material contained in the porous layer of a predetermined area is Xa, Xb, Xc, ..., Xn (g), and the true density of each constituent material is Da, Db, Dc, ..., Dn (g / cm 3 Substitute Xa, etc. in the above formula to represent the mass (g) of the constituent material used in forming the porous layer of a specified area. Substitute Da, etc. in the above formula to represent the true density (g / cm 3 ).
[0208] [Weight per unit area of barium compound particles]
[0209] The weight per unit area (g / m 2 ) refers to the mass of the barium compound particles contained in the porous layer per unit area, with the area of the porous layer being viewed from above being the unit area.
[0210] [Weight average molecular weight of polyvinylidene fluoride resin]
[0211] The weight average molecular weight of the entire polyvinylidene fluoride resin contained in the porous layer is a molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The polyvinylidene fluoride resin extracted from the porous layer or the polyvinylidene fluoride resin used to form the porous layer is used as a sample.
[0212] [X-ray CT]
[0213] - Fabrication of negative electrode -
[0214] Using a double-arm mixer, 300 parts by mass of artificial graphite as a negative electrode active material, 7.5 parts by mass of a water-soluble dispersion containing 40% by mass of a modified product of a styrene-butadiene copolymer as a binder resin, 3 parts by mass of carboxymethyl cellulose as a thickener, and an appropriate amount of water were stirred and mixed to prepare a negative electrode slurry. The negative electrode slurry was applied to both sides of a copper foil having a thickness of 10 μm, and pressed after drying to obtain a negative electrode having a negative electrode active material layer on both sides.
[0215] -Making the positive electrode-
[0216] A double-arm mixer was used to stir and mix 89.5 parts by mass of lithium cobalt oxide powder as a positive electrode active material, 4.5 parts by mass of acetylene black as a conductive aid, 6 parts by mass of polyvinylidene fluoride as a binder resin, and an appropriate amount of N-methyl-2-pyrrolidone to prepare a positive electrode slurry. The positive electrode slurry was applied to both sides of an aluminum foil with a thickness of 20 μm, dried, and pressed to obtain a positive electrode having a positive electrode active material layer on both sides.
[0217] -Preparation of samples for observation-
[0218] The positive electrode was cut into a rectangle of 30 mm × 50 mm, the negative electrode was cut into a rectangle of 30 mm × 50 mm, and the separator was cut into a rectangle of 34 mm × 54 mm. The positive electrode, separator, negative electrode, and separator were stacked in sequence to produce a laminate having three layers of positive and negative electrodes and five layers of separators. The laminate was inserted into a package made of an aluminum laminate film, and the inside of the package was made into a vacuum state and sealed using a vacuum sealer to obtain a sample for observation.
[0219] -X-ray CT-
[0220] X-ray CT uses a micro-focus X-ray CT system (inspeXio SMX-225CTFPD HR) manufactured by Shimadzu Corporation. Under the conditions of an X-ray tube voltage of 220 kV, an X-ray tube current of 100 μA, and an exposure time of 1 sec, a thickness-direction cross section of the laminate is photographed at the end of the observation sample. The grayscale value (GV) of the diaphragm is measured based on the X-ray CT image, and the GV is classified as follows. The larger the GV value, the better.
[0221] Level 5: GV is 37301 or above
[0222] Level 4: GV is 36501 or more and 37300 or less
[0223] Level 3: GV is 35701 or more and 36500 or less
[0224] Level 2: GV is 35251 or above and 35700 or below
[0225] Level 1: GV is 35250 or less
[0226] [Battery impact resistance (compression breaking strength)]
[0227] Prepare 10 test secondary batteries described later. Under a temperature of 20°C, the test secondary batteries are charged with constant current and constant voltage. Specifically, charge to 4.2V at 0.1C and keep at 4.2V for 3 hours. Next, place the test secondary battery on a horizontal platform with the positive electrode side on top and fix it with an adhesive tape. Place a spherical terminal with a diameter of 5 mm in the center of the test secondary battery, gradually lower it at a speed of 100 mm / min, and apply a load to the test secondary battery. Calculate the value of the load (unit: N) at the moment when the voltage of the test secondary battery drops to 3.5V, and calculate the average value of 10 batteries.
[0228] [Battery Cycle Characteristics (Capacity Retention Rate)]
[0229] Prepare 10 secondary batteries for the test described below. Charge and discharge the secondary batteries for the test for 500 cycles at a temperature of 40°C. For charging, perform constant current and constant voltage charging at 1C and 4.2V, and for discharging, perform constant current discharge at 1C and 2.75V cutoff. Divide the discharge capacity of the 500th cycle by the first discharge capacity, calculate the average value of 10 batteries, and use the obtained value (%) as the capacitance retention rate.
[0230] <Production of diaphragms and batteries>
[0231] [Example 1]
[0232] - Fabrication of diaphragm -
[0233] A polyvinylidene fluoride resin is dissolved in dimethylacetamide (DMAc) in such a manner that the resin concentration becomes 5.0% by mass, and barium sulfate particles are further stirred and dispersed to obtain a coating liquid (1). An appropriate amount of the coating liquid (1) is placed on a Meyer rod, and the coating liquid (1) is applied to both sides of the polyethylene microporous membrane. At this time, the coating is performed in such a manner that the coating amount on the surface and back of the polyethylene microporous membrane is equal. It is immersed in a coagulation liquid (DMAc: water = 50:50 [mass ratio], liquid temperature 40°C) to solidify the coating layer, and then it is washed in a water washing tank at a water temperature of 40°C and dried. In this way, a diaphragm having a porous layer formed on both sides of the polyethylene microporous membrane is obtained.
[0234] - Fabrication of negative electrode -
[0235] A double-arm mixer was used to stir and mix 300 parts by mass of artificial graphite as a negative electrode active material, 7.5 parts by mass of a water-soluble dispersion containing 40% by mass of a modified product of a styrene-butadiene copolymer as a binder resin, 3 parts by mass of carboxymethyl cellulose as a thickener, and an appropriate amount of water to prepare a negative electrode slurry. The negative electrode slurry was applied to one side of a copper foil having a thickness of 10 μm, and pressed after drying to obtain a negative electrode having a negative electrode active material layer on one side.
[0236] -Making the positive electrode-
[0237] A double-arm mixer was used to stir and mix 89.5 parts by mass of lithium cobalt oxide powder as a positive electrode active material, 4.5 parts by mass of acetylene black as a conductive aid, 6 parts by mass of polyvinylidene fluoride as a binder resin, and an appropriate amount of N-methyl-2-pyrrolidone to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum foil with a thickness of 20 μm, dried, and pressed to obtain a positive electrode having a positive electrode active material layer on one side.
[0238] -Battery production-
[0239] The positive electrode was cut into a rectangle of 30 mm × 50 mm, and the negative electrode was cut into a rectangle of 30 mm × 50 mm, and a lead tab was welded to each electrode. The separator was cut into a rectangle of 34 mm × 54 mm. The positive electrode, separator, and negative electrode were stacked in sequence. The stack was inserted into a package made of aluminum laminate film, and the electrolyte (1 mol / L LiPF6-ethylene carbonate: ethyl methyl carbonate [mass ratio 3:7]) was injected into the package to allow the electrolyte to penetrate into the stack. Next, a vacuum sealer was used to make the package vacuum and temporarily seal it, and a hot press was used to heat press the package along the stacking direction of the stack to bond the electrode to the separator. As for the hot pressing conditions, the temperature was set to 90°C, the load was set to 1 MPa, and the pressing time was set to 2 minutes. Next, a vacuum sealer was used to make the package vacuum and seal it to obtain a secondary battery for testing.
[0240] [Examples 2 to 13, Comparative Examples 1 to 12]
[0241] Each separator was produced in the same manner as in Example 1, except that the types and amounts of materials were changed as shown in Table 1. Then, each separator was used in the same manner as in Example 1 to produce a secondary battery for testing.
[0242] Table 1 shows the materials, compositions, physical properties, and evaluation results of each separator of Examples 1 to 13 and Comparative Examples 1 to 12.
[0243] "PVDF" in Table 1 is a binary copolymer of vinylidene fluoride and hexafluoropropylene, and is a polyvinylidene fluoride-based resin having a weight average molecular weight of 800,000.
[0244] The "meta-aramid" in Table 1 is poly(meta-phenylene isophthalamide).
[0245] [Table 1]
[0246]
[0247] The entire disclosure of Japanese Patent Application No. 2022-075141 filed on April 28, 2022 is incorporated into this specification by reference.
[0248] All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described.
Claims
1. A separator for a non-aqueous secondary battery, comprising: a porous substrate; and a porous layer, the porous layer being disposed on one side or both sides of the porous substrate and comprising a resin and barium compound particles, The average primary particle size of the barium compound particles contained in the porous layer is 0.30 μm or more and less than 0.50 μm. The volume ratio of the barium compound particles in the volume of the porous layer excluding pores is greater than 5 volume % and less than 70 volume %.
2. The non-aqueous secondary battery separator according to claim 1, wherein The barium compound particles include barium sulfate particles.
3. The non-aqueous secondary battery separator according to claim 1, wherein The resin includes a polyvinylidene fluoride-based resin.
4. The non-aqueous secondary battery separator according to claim 1, wherein The resin includes at least one selected from the group consisting of wholly aromatic polyamide, polyamideimide, poly-N-vinylacetamide, polyacrylamide, copolymer polyether polyamide, polyimide, and polyetherimide.
5. The non-aqueous secondary battery separator according to claim 1, wherein The weight per unit area of the porous layer is 2.0 g / m in total on both sides of the porous substrate. 2 Above 20.0g / m 2 the following.
6. The non-aqueous secondary battery separator according to claim 1, wherein The weight per unit area of the barium compound particles contained in the porous layer is 0.3 g / m in total on both sides of the porous substrate. 2 Above 19.0g / m 2 the following.
7. A non-aqueous secondary battery comprising a positive electrode, a negative electrode, and the non-aqueous secondary battery separator according to any one of claims 1 to 6 disposed between the positive electrode and the negative electrode, wherein the non-aqueous secondary battery obtains an electromotive force by doping and dedoping lithium ions.
